2020
DOI: 10.15537/smj.2020.10.25380
|View full text |Cite
|
Sign up to set email alerts
|

Screening for body dysmorphic disorder among patients pursuing cosmetic surgeries in Saudi Arabia

Abstract: To determine the prevalence of positive screening of body dysmorphic disorder (BDD) among patients seeking cosmetic surgeries in plastic surgery and oculoplastic surgery clinics. Methods: The survey of this cross-sectional study was self-administrated and distributed among adults pursuing cosmetic surgeries in plastic surgery and oculoplastic surgery clinics at King

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 34 publications
0
20
0
3
Order By: Relevance
“…This indicates that there are increased number of body dysmorphic disorder patients in Saudi Arabia. In comparison to other similar studies done in Saudi Arabia, a study that was done in Jeddah in 2020 showed nearly the same results with a percentage of 19.2% positive for BDD [6]. Another study conducted in Al Ahsa in 2019 reported a prevalence of 14.19% among people seeking facial plastic surgery [9].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This indicates that there are increased number of body dysmorphic disorder patients in Saudi Arabia. In comparison to other similar studies done in Saudi Arabia, a study that was done in Jeddah in 2020 showed nearly the same results with a percentage of 19.2% positive for BDD [6]. Another study conducted in Al Ahsa in 2019 reported a prevalence of 14.19% among people seeking facial plastic surgery [9].…”
Section: Discussionmentioning
confidence: 55%
“…In comparison with previous study done in Jeddah which showed that out of 344 participants (19.2%) had positive screening for BDD. Another study conducted in Al-Qassim region revealed that 58 out of 325 (18.6%) patients screened were positive with BDD [6,7].…”
Section: Sociodemographic Descriptorsmentioning
confidence: 98%
“…Dentre a busca por procedimentos estéticos devido a insatisfação, os que apresentam maior prevalência de pacientes com TDC são: a abdominoplastia, a lipoaspiração e a remoção de lesões de pele [23].…”
Section: Maioria Tem Queixas Compatíveisunclassified
“…A presença de TDC é uma relativa contraindicação para a realização de cirurgias plásticas estéticas, todavia o rastreio do distúrbio ainda se apresenta baixo [23]. Em estudo prospectivo realizado no Brasil, contrariando as opiniões acadêmicas, mostrou redução da insatisfação corporal com diminuição conjunta da intensidade dos sintomas do TDC após rinoseptoplastia [26].…”
Section: Maioria Tem Queixas Compatíveisunclassified
See 1 more Smart Citation